Benefits of Implementing the 5S Method in the Production Company Survey Results - Damian OSTROWSKI; Agnieszka PIASECKA – GLUSZAK (Communications of International Proceedings, 2020)
One of the basic objectives of implementing the lean management concept in companies is to achieve adequate operational efficiency, eliminate waste and reduce operating costs. Lean Management is the concept that focuses on the long-term perspective in its approach. One of the most frequently implemented methods of this concept is 5S. 5S is an easy to implement set of rules for eliminating waste, organizing the workplace or increasing employee involvement. The implementation itself is quite simple, however, the problem is to maintain the benefits resulting from the implementation activities in the long term. 5S comes from 5 Japanese words - Seiri (Sort), Seiton (Set in order), Seiso (Shine), Seiketsu (Stadardize) and Shitsuke (Sustain). The aim of the article is to present the results of a survey conducted in a production company regarding the effects of implementing this method in a factory in Wroclaw, Poland. The article discusses issues such as the evaluation of the method implementation, employee involvement, benefits of implementation processes
Keywords: Lean management; 5S; process optimization; employee involvement.